Prediction Red Chili Price Information in Bandung Use Smoothing Techniques - Istambul, Muhammad Rozahi; Abinowi, Egi (International Journal of Advanced Science and Technology, 2019)
In general, the need for consumption of people in Indonesia in making various types of main processed foods, it often adds one part of the cooking spices, namely chili. However, red chili commodity production in this society will experience ups and downs due to various factors. One of the main problems is the price of red chili, which is sometimes unstable or changes in pricing at the community level from year to year. This also happened in the city of Bandung, where time-series data on commodity prices for chili experienced instability. For the community as users not to panic, the government, in this case, the West Java Department of Agriculture will predict prices that can occur in the coming year. The data that has been held regarding the cost of communication in previous years will be the reference data in comparing the results of the actual price data regarding the data of the year to be predicted. In producing prediction data using a smoothing technique that is using The Holt-Winter’s method, this option is one of the forecasting methods related to time series data variables that have been previously owned. Through this research, it is expected to produce information about predicted price data, whether it is close to the actual price data that occurred.